Daily Mean Temperature Affects Urolithiasis Presentation in Seoul: a Time-series Analysis - Lee, SeoYeon (J Korean Med Sci, 2016)
This study aimed to investigate the overall cumulative exposure-response and the lag response relationships between daily temperature and urolithiasis presentation in Seoul. Using a time-series design and distributing lag nonlinear methods, we estimated the relative risk (RR) of urolithiasis presentation associated with mean daily temperature, including the cumulative RR for a 20 days period, and RR for individual daily lag through 20 days. We analyzed data from 14,518 patients of 4 hospitals emergency department who sought medical evaluation or treatment of urolithiasis from 2005-2013 in Seoul. RR was estimated according to sex and age. Associations between mean daily temperature and urolithiasis presentation were not monotonic. Furthermore, there was variation in the exposure-response curve shapes and the strength of association at different temperatures, although in most cases RRs increased for temperatures above the 13°C reference value. The RRs for urolothiasis at 29°C vs. 13°C were 2.54 in all patients (95% confidence interval [CI]: 1.67-3.87), 2.59 in male (95% CI, 1.56-4.32), 2.42 in female (95% CI, 1.15-5.07), 3.83 in male less than 40 years old (95% CI, 1.78-8.26), and 2.47 in male between 40 and 60 years old (95% CI, 1.15-5.34). Consistent trends of increasing RR of urolithiasis presentation were observed within 5 days of high temperatures across all groups. Urolithiasis presentation increased with high temperature with higher daily mean temperatures, with the strongest associations estimated for lags of only a few days, in Seoul, a metropolitan city in Korea.